Cancer Care Delivery and Women's Health - Sarah M. Temkin (Frontiers Research Topics, 2017)
Cancer care delivery refers to the multiple layers of the health care system that interact to affect outcomes for patients with cancer and the quality of that care. The factors included in the care delivery system that potentially alter outcomes include social dynamics, financing systems, organizational structures and processes, health technologies, provider and individual behaviors. Because women's health care has its own unique challenges, the intersection between cancer care delivery and women's health is to be examined in this Frontiers in Oncology issue. The unique opportunities and challenges of improving the health care system for women with breast and gynecologic cancers are to be explored in depth. We will visit many topics of cancer care delivery with the unique perspective geared towards the care of women's malignancies.